Western stereotype towards Somali muslim portraying islamophobia as seen in the black hawk down ( 2001 ) - Evans Ardi Pratama (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/irh,c.1